The Pattern of Injury from Road Traffic Accident Presenting at Emergency Department of Kathmandu Medical College - Kushwaha, Anu; Singh, Pankaj (Journal of Nepal Health Research Council, 2019)
Background: Road traffic accidents are the major public health problem. The objective of the study was to analyze road traffic accidents presenting in Kathmandu Medical College Emergency Department. Methods: The data from all consecutive road traffic accident cases brought to Emergency Department Kathmandu Medical College Teaching Hospital were collected from 2018 Jan-2018 June. Factors like age of the patients, time of the accident, influence of illicit substances and type of injury were documented. Results: Males (74) were common victims than the females (26). Eldest patient was 65 years of the age while youngest patient was 4 years. Most common type of injury was fracture in male 28 (37%)and laceration in females8 (38%). Alcohol intoxication was evident by positive alcohol smell test in 10 (13.6%) males and 6(23%) females. Conclusions: Road traffic accidents are major health concern in Kathmandu Medical College Teaching Hospital and preventive measures should be considered to reduce such health burden. Keywords: Alcohol; Injury;Pattern; RTA.